Recuperación del patrimonio cultural inmaterial de la comunidad Lupaxí Grande, parroquia Santiago de Quito, cantón Colta, provincia de Chimborazo - Chucho Mayanza, Freddy Paul (2018)
The present research work titled recovery of intangible cultural heritage of the Lupaxí Grande community, Santiago de Quito parish, Colta canton, Chimborazo province, is the result of the concern in order to establish the intangible cultural heritage of this community, it has a large variety of intangible cultural heritage that its inhabitants practice in their daily lives; the main objective of this research is to collect the intangible cultural heritage of the Lupaxi Grande community and to register, the methodology of the INPC, the intangible cultural heritage that is not registered in the SIPCE platform (INPC) of the Lupaxí Grande community. The techniques used were the interview and direct observation, which permit to get the respective conclusions. The applied instruments were the question guides, the same ones that facilitated in order to know the intangible cultural heritage that has been keep in the memory of the inhabitants of this community, the applied methodology allowed to reach the logic of scientific knowledge with respect to heritage and culture, the research design is qualitative where it allowed to observe the phenomenon as was presented in the context, the type of research is the descriptive through them were, analyzed and interpreted the results obtained through the instrument that were applied to the adults of the Lupaxí Grande community, and in this way find the results that allowed reaching the respective conclusions.